74.8k views
4 votes
(3w-5)(1+w)=0
I need help pls!!

User Yellavon
by
5.2k points

2 Answers

2 votes
Reorder the terms:

(-5 + 3w)(1 + -1w) = 0


Multiply (-5 + 3w) * (1 + -1w)



(-5(1 + -1w) + 3w * (1 + -1w)) = 0

((1 * -5 + -1w * -5) + 3w * (1 + -1w)) = 0

((-5 + 5w) + 3w * (1 + -1w)) = 0

(-5 + 5w + (1 * 3w + -1w * 3w)) = 0

(-5 + 5w + (3w + -3w2)) = 0


Combine like terms: 5w + 3w = 8w

(-5 + 8w + -3w2) = 0


Solving

-5 + 8w + -3w2 = 0


Solving for variable 'w'.


Factor a trinomial.

(-5 + 3w)(1 + -1w) = 0
User Chambeur
by
5.3k points
4 votes
you need to set both of them equal to zero to find what w is. so its 3w-5=0 you add 5 to get w by itself so then its 3w=5 and then divide by 3 so w= 5/3
1 + w = 0 so then you subtract one to get to the other side so w = -1

the final solution is {5/3, -1}
User Bcherny
by
5.9k points